Dynamical enhancement of spatial entanglement in massive particles - Lubasch, Michael; Mintert, Florian; Wimberger, Sandro (Physical review. A, Atomic, molecular, and optical physics, 2011)
We discuss dynamical enhancement of entanglement in a driven Bose-Hubbard model and find an enhancement of two orders of magnitude from the ground state value which is robust against fluctuations in experimental parameters.